Pemanfaatan Hak Eksplorasi Ruang Angkasa Menurut Outer Space Treaty 1967 oleh Program Ruang Angkasa Uni Emirat Arab - Farellino, Nichollas; Sidik, Hasan (Jurnal ICMES, 2023)
United Arab Emirates (UAE) is actively using its space exploration rights. In achieving national space goals, congested geostationary orbit (GSO) and first come, first served practice are issues that threaten the UAE as a newcomer in space. UAE must utilize its space rights per the international regime, including when dealing with congested GSO issues. This study aims to determine the compliance of UAE's space exploration rights utilization in dealing with congested GSO issues according to the international regime. This study uses international regime theory by Krasner and astropolitics by Everett Dolman through a case study qualitative method. The results indicate that from an astropolitic theory, the UAE has utilized its rights by the prevailing regime. UAE mainly uses the rights from OST 1967 because they're more general and applicable. Provisions in other space regimes, agreements, and conventions still need to be applied to the UAE, which makes these rights only slightly relevant to the UAE's efforts to deal with the GSO issue. However, the UAE may benefit from these rights in the future as the issue becomes more complex. UAE has been addressing the issue of congested GSO by conducting space activities in accordance with international regimes.